2015
DOI: 10.1002/rcm.7153
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of product ions by electrospray ionization and quadrupole time‐of‐flight mass spectrometry to support regulatory analysis of veterinary drug residues in foods. Part 2: Benzimidazoles, nitromidazoles, phenothiazines, and mectins

Abstract: Structural characterization of the product ions selected for identification and quantification of veterinary drug residues is important information for regulatory monitoring programs in defense of regulatory enforcement actions. This study has allowed structural elucidation of 84 MS/MS product ions previously selected for the LC/MS/MS analysis of 28 drug analytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…ESI‐MS/MS usually causes heterolytic cleavage of the precursor ion to produce even‐electron (EE) structures but, depending on the groups attached to the molecule, an odd‐electron (OE) product ion can be formed after the elimination of a neutral radical. The presence of sulfur or nitro groups can lead to homolytic bond cleavage causing formation of OE structures, as has been reported before for positive ions . The OE process also occurs in negative mode .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…ESI‐MS/MS usually causes heterolytic cleavage of the precursor ion to produce even‐electron (EE) structures but, depending on the groups attached to the molecule, an odd‐electron (OE) product ion can be formed after the elimination of a neutral radical. The presence of sulfur or nitro groups can lead to homolytic bond cleavage causing formation of OE structures, as has been reported before for positive ions . The OE process also occurs in negative mode .…”
Section: Resultsmentioning
confidence: 59%
“…This work constitutes part 3 of the ongoing study to characterize the structures of the three selected product ions in the analytical method for monitoring 130 veterinary drugs in food animal tissues. Parts 1 and 2 reported the structural elucidation of the selected product ions for 92 veterinary drugs . Our intent now is to present structural data for the 72 product ions of 24 veterinary drugs corresponding to the anthelmintic, thyreostat, and flukicide groups.…”
mentioning
confidence: 99%
“…Mass fragmentation studies revealed that the m/z of FOD1 fragmented into product ions of m/z 199 on loss of 'OH'. [34][35][36] The product ion of m/z 199 further fragmented into 167 on loss of 'S' [30][31][32][33][34] (Table 2, Fig. 8).…”
Section: Structural Confirmation Resultsmentioning
confidence: 99%
“…In addition, availability of commercial software for spectra interpretation and public compound databases can help in elucidation of structures of product ions, but this approach should be considered with caution and some of these limitations have been described by Wright et al [15]. Previously, we conducted structural characterization of product ions for 120 veterinary drugs with ESI quadrupole time-of-flight (Q-TOF) MS [7,8,9]. In the present study, a Q-Orbitrap instrument was used for characterization of product ions to differentiate isomeric pesticides.…”
Section: Resultsmentioning
confidence: 99%
“…Combining this information with literature searches, databases, and data interpretation helps with the assignment of product ions structures. Currently, few published manuscripts on the analysis of contaminants report fragment/product ions with elucidation of the corresponding structures [6,7,8,9,10]. Yet, elucidation of ion structures is important to provide further support for elimination of false positive findings.…”
Section: Introductionmentioning
confidence: 99%